Development the Achievement of Critical Reading Comprehension by Learning to Read with a 6-Steps Ladder Technique Together with Online Exercises on the Platform Liveworksheets Grade 2 Secondary Education School Students - Minthayak, Phitchaon; Ongartvanit, Namthip (Humanities and Social Sciences Nakhonsawan Rajabhat University Academic Journal, 2023)
The objectives of this research were 1) to develop reading comprehension through the 6-step ladder technique of reading style learning together with online exercises on the live worksheet platform, 2) to compare reading comprehension achievements before and after learning, and 3) to study student satisfaction The sample group was 40 students in grade 2/7 of Nakhon Sawan School, semester 2/2022 by specific selection method. There were 4 types of tools used: 1) Reading Comprehension Learning Plan, 2) Online exercises on the live worksheet platform,3) Reading Comprehension Test, and 4) Satisfaction Assessment. The statistics used in data analysis were mean and standard deviation. The findings of this research as following : 1) The consistency index of the plan was 0.80, the level of suitability in the elements of the plan was at the highest level ( = 4.76, S.D. = 0.46) 2) The test scores after the learning management of the students were higher than before the learning management with statistically significance at the .05 level, 3) There was a high level of satisfaction ( = 3.86, S.D. = 0.80).